Pola Komunikasi Nabi terhadap Pelaku Maksiat: Analisis Komunikasi dalam Hadis Tentang Pengakuan Pelaku Zina - Jamal, Fitah Jamaludin (Icon: Islamic Communication and Contemporary Media Studies, 2023)
Communication is one of the ways humans express themselves to others, either through speech or writing. However, on the other hand, there are agreed-upon rules and norms used in communication. In certain situations, proper communication can save the communicator, while poor communication can harm them in other situations. It is not uncommon for someone to speak freely to others without limits, especially if the other person is in a guilty state. This is different from what was taught by the Prophet when he communicated with the perpetrators of adultery who confessed to him. Based on this issue, the research questions in this paper are formulated as follows: 1) What is the communication pattern of the Prophet? 2) How did the Prophet communicate with the confessors of adultery? This study was conducted using a qualitative literature review method and using sociological theory. The findings from this study suggest that different treatments are given to the same case, and communication is done by using kind words, honesty, advising in goodness, and avoiding slander.